An Overview of Community Pharmacy in Malanje City, Angola: Service Quality and Safety Measurements - Chimbuco , Bernardo Nicodemo; Ferreira, Mateus Alfredo; Sacomboio, Euclides Nenga Manuel; Ekundi-Valentim , Eduardo (Recent Updates in Disease and Health Research Vol. 7, 2024)
Background and Aim: This study aimed to describe the community pharmacies in the city of Malanje, focusing on staff, facilities and equipment, to propose actions that can be implemented to improve the quality of services, and consequently the safety of the population. A community pharmacy, sometimes referred to as a retail pharmacy, is the most prevalent kind of pharmacy where customers can obtain prescription drugs and health-related information. Good pharmacy practices must be followed, and this starts with the environment in the community pharmacy and the credentials of the employees who work there. Methods: A cross-sectional observational study with a quantitative and qualitative approach. Through a simple random sampling technique, 20 pharmacies were selected from a universe of 73 reported by official authorities. Results: No pharmacist was acting in the local pharmacies, and their activity was supported by other professionals, particularly intermediate nursing technicians (57%). The majority of pharmacies were located in peri-urban areas, and Angolan legislation was not followed in the functional areas, utilities, or equipment they used. Furthermore, it was noted that certain medications that are not available over-the-counter were distributed. The conclusion is that community pharmacies in Malanje operate illegally, which poses a serious threat to the observance of pharmacy service requirements.